2022
DOI: 10.1111/mcn.13253
|View full text |Cite
|
Sign up to set email alerts
|

Improving nutrition budgeting in health sector plans: Evidence from India's anaemia control strategy

Abstract: In India, 15 nutrition interventions are delivered and financed through the National Health Mission (NHM). Programmatic know-how, however, on tracking nutrition budgets in health sector plans is limited. Following the four phases of the budget cycle-planning, allocations, disbursements and expenditure, this paper presents a new method developed by the authors to track nutrition budgets within health sector plans. Using the example of the Anemia Mukt Bharat (AMB) or Anemia Free India strategy, it reports prelim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Anaemia Mukt Bharat (anaemia free India) was launched recently by the Government of India to reduce the prevalence of anaemia by 3% points yearly among children, adolescents, and women in the reproductive age (15–49 years) from 2018 to 2022 [ 36 ]. However, over the past decade, a drop of mere 0.7 percentage points was experienced by women (from 62.5% in 2006 to 61.8% in 2016) in West Bengal, indicating the failure of these targets [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Anaemia Mukt Bharat (anaemia free India) was launched recently by the Government of India to reduce the prevalence of anaemia by 3% points yearly among children, adolescents, and women in the reproductive age (15–49 years) from 2018 to 2022 [ 36 ]. However, over the past decade, a drop of mere 0.7 percentage points was experienced by women (from 62.5% in 2006 to 61.8% in 2016) in West Bengal, indicating the failure of these targets [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, based on a literature review we identified seven key correlates of utilization of antenatal services, i.e. place of residence, education and age of women, wealth, number of children, social group and religion ( Singh et al , 2012 ; Saad–Haddad et al , 2016 ; Okedo-Alex et al , 2019 ). Apart from unadjusted estimates, difference-in-difference estimates were calculated after adjusting for all these socio-economic correlates using the ‘diff’ command in Stata 15.…”
Section: Methodsmentioning
confidence: 99%
“…The Indian government has launched several anti-anaemia initiatives over the years, including the National Iron Plus Initiative (NIPI) [3], which provides iron and folic acid supplements to pregnant and lactating women and children. The 'Anaemia Mukt Bharat' (AMB) strategy or 'Anaemia-Free India' was launched in 2018 to reduce anaemia in vulnerable age groups especially women, children, and adolescents through a life cycle approach that includes preventive and curative mechanisms [3].…”
Section: Introductionmentioning
confidence: 99%
“…The Indian government has launched several anti-anaemia initiatives over the years, including the National Iron Plus Initiative (NIPI) [3], which provides iron and folic acid supplements to pregnant and lactating women and children. The 'Anaemia Mukt Bharat' (AMB) strategy or 'Anaemia-Free India' was launched in 2018 to reduce anaemia in vulnerable age groups especially women, children, and adolescents through a life cycle approach that includes preventive and curative mechanisms [3]. The significance of community anaemia screening lies in its ability to detect and address anaemia at an early stage, particularly in vulnerable populations, improving overall health outcomes and reducing the burden of this widespread condition.…”
Section: Introductionmentioning
confidence: 99%